Association analysis of grassland composing plant species based on ecological claims - Harcsa, Marietta; Szemán, László (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
We checked the evaluation of grass stand, which was established as a species-rich mixture, in a ten-years continuance experiment. In the established mixtures there were 17 wild-cropped and meadows growing adaptable dicotyledonous (wildflower), 2 vexillaries and 7 grasses species. We established in the experiment three kind of mixtures in three iterations. The measure of parcel patches were 6*5 meter, with 0,5 meter disjunctive area. The reservation of the grassland was with extensive methods. After the year of establishment we made assessment for the botanical covers per months, then twice a year, and then once a year. We used simple comparison in the analysis, then we evaluated the TWR values stressed with rates of the botanical covers. At the end of the ninth year there were 9 species from the established 26 species in the stand. The first question of the experiment was that what ecological demands owned the residual species in the experiment’s areas. Checking the temperature demand (T), water demand (W) and soil reaction (R) cleared up, that the residual species have similar ecological demands. Adapting the stressed method, the grassland society showes unique results of the groundtest, which differ from the established one. Summing our results, we appointed that the soil aptitude of the areas and the habitat demand of the society are equal. This method is adaptable for developing the habitat aptitude analogue plant stand before establishing species rich grassland.